Populist Parties and Pork-Barrel Politics in Indonesia: The Erosion of Political Morality - Jubaidi, Didi; Khoirunnisa, Khoirunnisa (Soshum: Jurnal Sosial dan Humaniora, 2025)
The phenomenon of populist parties and "pork barrel" politics in Indonesia often emerges with promises of radical change and claims to represent the "voice of the people." However, in practice, these parties frequently become entangled in corruption, nepotism, and clientelism, undermining political integrity and public trust. "Pork barrel" politics in Indonesia refers to the strategic and often inequitable distribution of state resources—such as regional development projects or social assistance programs—used to secure political support. This study examines how these practices erode not only political morality and democratic integrity but also the social and psychological underpinnings of public trust in government institutions. Employing a qualitative approach with case studies and document analysis, the research explores corruption cases involving public officials and the broader societal impacts of "pork barrel" politics. The findings reveal that these practices have not only degraded the ethical standards of political actors but have also fostered widespread public cynicism, exacerbating a psychological sense of distrust and disillusionment with the political system. To address these challenges, the study highlights the need for systemic reforms, including greater transparency in budget allocation, robust legal enforcement against corruption, and political education that prioritizes ethical behavior, civic responsibility, and trust-building. These efforts are vital for restoring public confidence, strengthening democratic values, and fostering a more morally grounded political culture in Indonesia.